A CFD/CSD coupled method with high order and its applications in flow induced vibrations of tube arrays in cross flow. (August 2019) - Tang, Di; Bao, Shiyi; Luo, Lijia; Zhu, Hai; Cui, Hao
Highlights: A closely CFD/CSD coupled method with 4 th order was proposed. Flow dynamics were studied to find out a dominant frequency. Both the cylinder nature frequency and dominant frequency of flow are crucial. Abstract: Wear and tear are the most common failures of tubes in cross-flow during long time operation of a steam generator due to the fluid induced vibrations. A fluid-elastic approach with high order was developed by coupling the CFD method and the CSD method. In the method, fluid forces were predicted by the CFD method followed by structural response calculations, and data were transferred via fluid-structure interaction interface. The unsteady flow through normal triangular cylinder arrays with one single tube undergoing self-excited oscillations was simulated by the proposed method. Lifts, displacement and velocity of the particular cylinder were obtained followed by calculations of the corresponding frequency spectrums. Results showed that the proposed method can predict the flow induced vibrations with high accuracy. When the natural frequency of the cylinder increased to the dominant frequency of the flow, an abrupt increment of vibrational velocity was observed.